The effect of variation in E7018 electrode current on the bending strength of carbon steel material - Muhammad Arga Syahandra; Saifuddin; Azwinur (Journal of Mechanical Engineering and Fabrication, 2024)
Welding is one of the essential metal joining methods in modern industry. In carbon steel welding such as ASTM A36, SMAW is often chosen because of its ability to produce strong joints with economical operating costs. However, the mechanical properties of the welded joints on this steel are greatly influenced by the welding process parameters, such as the type of electrode and the welding current setting. The purpose of this study was to evaluate the effect of variations in welding current with E7018 electrodes on the bending properties of ASTM A36 carbon steel material. The stages of the study were material welding, visual and penetrant non-destructive tests and bending tests. The results of the study showed that the best results were obtained on the cover side with a current of 110A, where the heat generated was sufficient to create a strong and flexible joint against deformation. While on the root pass side the highest bending value was at a current of 120A